CONTRACTOR’S PERSPECTIVE ON EXECUTION METHOD IMPACT TO COST OVERRUN IN BALI’S BUILDING CONSTRUCTION - Ni Made Rika Diandra Saraswati; I Putu Artama Wiguna (Jurnal Ilmiah Teknik Sipil, 2024)
Cost overruns is a common issue frequently encountered in the construction sector in Indonesia. Improper management of execution methods and project resources (equipment, materials, and labor) used can lead to cost overrun. Focusing on building construction projects in Bali from the contractor's perspective, this research employed SEM-LISREL to assess the relationship between execution methods, equipment, materials, labor, and cost overruns. The model development process involved identifying measurement items derived from existing literature regarding execution methods, equipment, materials, labor, and cost overruns. Through a questionnaire distributed to 200 contractor employees. The results show a significant impact of execution methods on cost overruns, mainly through intermediary variables such as materials and labor. In contrast, equipment has no significant influence in either the mediation or direct relationship with cost overruns. This study highlights the significant impact of materials, quantified at 4.63, on cost overruns in construction projects. Labor is found to contribute to cost overrun in construction endeavors by 2.36. Moreover, the analysis underscores that the cost overrun can be linked to various indicators associated with encompassing material delivery, material availability, manipulation of material, as well as labor productivity and quantity. By considering these aspects and implementing appropriate strategies, contractors can optimize resource efficiency, control project costs, and ultimately enhance their competitiveness and profitability in the construction industry.